a pH-metric speciation and anti-diabetic study of oxovanadium (IV) amino acid derivatives - Gundhla, Isaac Zvikomborero (Rhodes University, Faculty of Science, Department of Chemistry, 2011)
Novel oxovanadium(IV) complexes of glycine, ÊŸ-alanine, 1-methylimidazole-2-carboxylic acid, imidazole-2-caboxylic acid and imidazole-4-carboxylic acid were synthesized and isolated in the solid state. The ligands and complexes were characterized by elemental analysis, melting point, NMR, IR and UV-vis spectroscopy. The IR studies showed that glycine and ÊŸ-alanine coordinate monodentately through the amine nitrogen whilst the imidazole-carboxylic acid derivatives assume a bidentate chelation. The electronic spectroscopic studies indicate distorted octahedral geometry for the oxovanadium complexes of amino acids and a square pyramidal geometry for oxovanadium(IV) complexes of imidazole carboxylic acid derivatives. The reaction of vanadyl (VO2+) with glycine, ÊŸ-alanine, imidazole-2-cabrboxylic acid, imidazole-4-carboxylic acid and 1-methylimidazole-2-carboxylic acid was studied in aqueous solution by pH-potentiometry under oxygen and carbon dioxide-free conditions. The data obtained from these titrations were used to calculate the protonation and stability constants. The results showed that all ligands are suitable for bidentate coordination in the formation of monomeric species although the solid state studies of the oxovanadium(IV) complexes of amino acids showed a monodentate coordination. The overall stability constants for the (VIVO)-ÊŸ-alanine system (log Î²120 = 18.27(6)), (VIVO)-glycine system (Î²120 = 17.22(6)), (VIVO)-imidazole-4-carboxyic acid (Î²120 = 11.38(8)), (VIVO)-imidazole-2-carboxylic acid (Î²120 = 11.62(6)) and (VIVO)-1-methylimidazole-2-carboxylic acid (Î²120 = 15.49(9)) were obtained. The calculations for the species distribution in the experimental pH range showed that the neutral bis-coordinated complexes are dominant over the biological pH range. The glucose uptake effect of oxovanadium(IV) complex of ÊŸ-alanine, imidazole-4-carboxylic acid, imidazole-2-carboxylic acid and 1-methylimidazole-2-carboxylic acid was investigated using 3T3-L1 adipocytes, Chang liver and C2C12 muscle cells at various concentrations. The compounds had significant glucose uptake on Chang liver cells only at a concentration of 0.1-10 Î¼M whilst in the C2C12 muscle and 3T3-L1 cells the compounds showed little to no activity probably due to the lower concentrations employed as a result of the cytotoxicity of these compounds on these two cell lines.
Keywords: Uncatalogued